United Nations sanctions and the rule of law / by Jeremy Matam Farrall. - Farrall, Jeremy Matam (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2007)
The United Nations Security Council has increasingly resorted to sanctions as part of its efforts to prevent and resolve conflict. In this 2007 book, Farrall traces the evolution of the Security Council's sanctions powers and charts the contours of the UN sanctions system. He also evaluates the extent to which the Security Council's increasing commitment to strengthening the rule of law extends to its sanctions practice. The book identifies shortcomings in respect of key rule of law principles and advances pragmatic policy-reform proposals designed to ensure that UN sanctions promote, strengthen and reinforce the rule of law. In its appendices United Nations Sanctions and the Rule of Law contains summaries of all 25 UN sanctions regimes established to date by the Security Council. It forms an invaluable source of reference for diplomats, policymakers, scholars and advocates.